Induced Pluripotent Stem Cells to Model Human Fibrodysplasia Ossificans Progressiva - Jie Cai; Valeria V. Orlova; Xiujuan Cai; Elisabeth M.W. Eekhoff; Keqin Zhang; Duanqing Pei; Guangjin Pan; Christine L. Mummery; Peter ten Dijke (Stem Cell Reports, 2015)
Fibrodysplasia ossificans progressiva (FOP) is a rare disease characterized by progressive ossification of soft tissues, for which there is no effective treatment. Mutations in the bone morphogenetic protein (BMP) type I receptor activin receptor-like kinase 2 (ACVR1/ALK2) are the main cause of FOP. We generated human induced pluripotent stem cells (hiPSCs) from FOP patients with the ALK2 R206H mutation. The mutant ALK2 gene changed differentiation efficiencies of hiPSCs into FOP bone-forming progenitors: endothelial cells (ECs) and pericytes. ECs from FOP hiPSCs showed reduced expression of vascular endothelial growth factor receptor 2 and could transform into mesenchymal cells through endothelial-mesenchymal transition. Increased mineralization of pericytes from FOP hiPSCs could be partly inhibited by the ALK2 kinase inhibitor LDN-212854. Thus, differentiated FOP hiPSCs recapitulate some aspects of the disease phenotype in vitro, and they could be instrumental in further elucidating underlying mechanisms of FOP and development of therapeutic drug candidates.